Augmenting physical 3D models with projected information to support environmental knowledge exchange. (November 2019) - Fisher, Rohan; Heckbert, Scott; León Villalobos, José María; Sutton, Stephen
Abstract: Participatory GIS has emerged as a useful tool for participatory planning and collaborative decision making. Many participatory GIS approaches are low-tech methods, including using physical objects such as 3D topographical models to assist with landscape recognition. More recently, physical 3D models have been augmented with light projection of digital landscape information and simulation models. Here we describe approaches currently being employed using 3D Projection-Augmented Landscape Models (3DPALM). We also explore the potential of emerging approaches that bridge traditional 3D participatory GIS and geosimulation models. Case studies are presented from Australia, Mexico and Canada that use physical 3D landscapes augmented with geosimulation models to support participatory planning, education and cross-cultural knowledge exchange. The work described in this paper suggests there are significant opportunities for the wider use of 3DPALM application to support a broad range participatory planning applications. Highlights: 3D landscape models with light projection have diverse methods. Effectively supports participatory GIS and planning applications. The utility in low resource and remote contexts shown. Evolving technology providing opportunities for the wider use of this approach.